Marital Quality and Hardiness on Parenting Stress in Couples with Children on the Autistic Spectrum - Istikomah, Fatonah; Nurhayati, Siti Rohmah (Psychological Research and Intervention, 2022)
Literature review and preliminary research show that there is a tendency for parents who have children with the autistic spectrum to experience parenting stress. On the other hand, there is a tendency for married couples who are not united and have low marital quality, and parents are discouraged when caring for children with the autistic spectrum. Therefore, this study aims to examine the effect of marital quality and hardiness on parenting stress in parents who have children on the autistic spectrum. Quantitative research with a survey method, the research sample amounted to 31 respondents who were determined by the saturated sampling method. The research used instruments, namely, the parenting stress index-short form (PSI-SF) scale by Abidin, the Dispositional Resilience Scale (DRS-15) by Bartone, and the marriage quality scale by Nurhayati. The data analysis technique is multiple linear regression analysis. The results of the study, the quality of marriage has no effect on parenting stress with a value of t = 0.288; sig= 0.776.personality Hardiness has an effect on parenting stress with a value of t= -2.155; sig= 0.040. Marital quality and hardiness have no simultaneous effect on parenting stress on parents with autistic spectrum children with a value of F= 2,632; sig= 0.090